Training on Preparing Financial Reports and Filling Out Annual SPT at Toko Serasi - Satriawan Adinugroho; Hasim As’ari (Jurnal Pengabdian Masyarakat Bestari, 2024)
This community service activity aims to improve partners' understanding of preparing financial reports based on the Akuntansiku application and reporting Annual Tax Returns online. The implementation process includes observation, socialization, training, and evaluation methods, with the delivery of materials on basic accounting concepts, Akuntansiku application features, preparing financial reports, and filling out Annual Tax Returns online. The results of the activity show an increase in partners' understanding of preparing financial reports based on the Akuntansiku application and reporting Annual Tax Returns online, which has positive implications for the sustainability of their businesses and compliance with tax obligations.